2001
DOI: 10.1007/bf02375472
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductivity and battery characteristic studies on PEO+NaClO3 polymer electrolyte

Abstract: Abstract. Solid polymer electrolyte films based on poly (ethylene oxide) PEO complcxed with NaCIO3 have been prepared by a solution-cast technique. The solvation of Na § ion with PEO is confirmed by XRD and IR studies. Measurements of the a.c. conductivity in the temperature range 308 -378 K and the transference numbers have been carried out to investigate the charge transport in this polymer electrolyte system. Transport number data show that the charge transport in this polymer electrolyte system is predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Hassan et al [ 11 ] reported the ionic conductivities of the PEO-KOH-H 2 O ASPEs reaching the level of 10 −5 S·cm −1 with using in Ni-MH batteries. Chandrasekaran et al [ 12 ] prepared an ASPE based on PEO + NaClO 3 for using in Ni-MH batteries, and the ionic conductivity reached 10 −4 S·cm −1 . Although the PEO-based ASPEs could form a dimensionally stable membrane, but the conductivity was still too low for application in electrochemical devices [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al [ 11 ] reported the ionic conductivities of the PEO-KOH-H 2 O ASPEs reaching the level of 10 −5 S·cm −1 with using in Ni-MH batteries. Chandrasekaran et al [ 12 ] prepared an ASPE based on PEO + NaClO 3 for using in Ni-MH batteries, and the ionic conductivity reached 10 −4 S·cm −1 . Although the PEO-based ASPEs could form a dimensionally stable membrane, but the conductivity was still too low for application in electrochemical devices [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has been referred to as Optimum Conducting Composition (OCC). The increase in conductivity is due to the increase in degree of amorphousity, which can be explained by the various models [3][4][5]. FTIR is also a powerful technique to confirm the complexation between polymer and salts.…”
Section: Resultsmentioning
confidence: 99%
“…Ion conduction in polymers was reported for the first time in 1973 and the first practical SPE battery based on 'Poly (ethylene oxide) (PEO) -Li + -ion salt complex' was demonstrated in 1979 [7]. Since then, a large number of solid polymer electrolytes (SPEs) and nanocomposite polymer electrolytes (NCPEs) have been reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. SPE/ NCPE films are prepared usually by solutioncast method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many sodium-ion-conducting polymer electrolytes based on polyethylene oxide (PEO), polypropylene oxide (PPO), and poly-bismethoxyethoxyethoxyphospanzene complexed with NaSCN, NaI, NaClO 4 , NaCF 3 SO 3 , NaPF 6 , NaYF 4 , NaNO 3 , and NaClO 3 [5][6][7][8][9][10][11][12][13] have been reported earlier. Vanadium pentoxide (V 2 O 5 ) is a powerful cathode material having reasonably high-voltage and high-discharge capacity [14][15][16].…”
Section: Introductionmentioning
confidence: 99%